2021
DOI: 10.1177/1321103x211009323
|View full text |Cite
|
Sign up to set email alerts
|

Culturally responsive and meaningful music education: Multimodality, meaning-making, and communication in diverse learning contexts

Abstract: Music is learned and taught in multiple ways dependent on the socio-cultural contexts in which learning occurs. The processes employed by music teachers have been extensively explored by music educators and ethnomusicologists in a range of contexts, although there has been limited research into which modes are most predominantly used in different socio-cultural contexts. Further, it is unknown how students make meaning in these different contexts. This article presents three distinct music learning and teachin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Considering Barton and Riddle's (2021) argument that varied modes of communication in the classroom are important in making music education meaningful for diverse groups of learners, different forms of agency might be fruitful as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering Barton and Riddle's (2021) argument that varied modes of communication in the classroom are important in making music education meaningful for diverse groups of learners, different forms of agency might be fruitful as well.…”
Section: Discussionmentioning
confidence: 99%
“…The question is whether these forms of agency are all fruitful and relevant for students’ future music teaching in schools. Considering Barton and Riddle’s (2021) argument that varied modes of communication in the classroom are important in making music education meaningful for diverse groups of learners, different forms of agency might be fruitful as well.…”
Section: Discussionmentioning
confidence: 99%
“…To address issues of cultural diversity in music education, international educators have advocated using CRT to facilitate the development of students' ethnic and cultural identities (e.g. Barton & Riddle, 2021;Bond, 2017;Bond & Russel, 2019;Crawford, 2020;Fitzpatrick, 2022;Lindl, 2018;Locke & Prentice 2016;Palmer et al, 2021;Shaw, 2014Shaw, , 2016Shaw, , 2020. Gay (2010) defined CRT as an approach that uses 'the cultural knowledge, prior experiences, frames of reference and performance styles of ethnically diverse students to make learning encounters more relevant to and effective for them ' (p. 31).…”
Section: Culturally Responsive Music Teachingmentioning
confidence: 99%
“…In addition to forging a link between students’ musical experiences at home and at school, teachers play an important role in students’ ethnic identity development (e.g. Barton & Riddle, 2021; Bond & Russel, 2019; Crawford 2020; Fitzpatrick, 2022; Lindl, 2018; Shaw, 2016). Teachers can play the roles of co-learners, listeners, facilitators, organisers, culture bearers, friends or parental figures during the music learning process, thereby promoting students’ ethnic identities (Fitzpatrick, 2022; Lindl, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Music carries a set of unique codes and patterns, which are universally understood (Juslin, 2013;Whiteford et al, 2018). Music, therefore, can be a core feature of social celebrations, such as weddings, as a means of cultural expression and maintenance through the ceremony (Barton & Riddle, 2021). According to research conducted by Mehr et al (2019), they found that, across societies, music is associated with behaviors such as infant care, healing, dance, and love (among many others, like mourning, warfare, processions, and ritual), and they discovered that songs that share behavioral functions tend to have similar musical features: "[...] music pervades social life in similar ways all around the world " (Mehr, et al, 2019:1).…”
Section: Objectives Of the Studymentioning
confidence: 99%